Chondroblastoma of the Knee Treated with Resection and Osteochondral Allograft Reconstruction - Judd Fitzgerald; Cory Broehm; David Chafey; Gehron Treme (Case Reports in Orthopedics)
Case. This case report describes the operative management of 16-year-old male with a symptomatic chondroblastoma of the distal femur with breach of the chondral surface. Following appropriate imaging and core needle biopsy, the diagnosis was confirmed histologically. The patient then underwent intralesional curettage and osteochondral allograft reconstruction of the defect. At one-year follow-up the patient was pain-free and has obtained excellent range of motion. There is radiographic evidence of allograft incorporation and no evidence of local recurrence. Conclusion. Osteochondral allograft reconstruction is an effective option following marginal resection and curettage of chondroblastoma involving the chondral surface of the distal femur.